Automated portfolio trading systems forensic forecast audit. (1st January 2014) - Rushinek, Avi; Rushinek, Sara
Algorithmic trading systems strategies frequently deal with forecasting the profitability of the trade using regression analysis. Yet many of the elementary accounting textbook authors confuse very basic issues related to regression analysis. Forensic accounting tests such confusions in the courts and tries to clarify this as expert witnesses try to estimate the damages using a 'but-if' regression analysis. This paper takes some of these lessons and tries to evaluate them to see whether they apply to automated international portfolio trading systems strategies.